2013
DOI: 10.11118/actaun201361030677
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water extracts of selected turfgrass species on germination and initial growth of Poa annua L.

Abstract: KOVÁR PETER, VOZÁR ĽUBOŠ, JANČOVIČ JÁN:The infl uence of water extracts of selected turfgrass species on germination and initial growth of Poa annua L. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 3, pp. 677-681 The eff ect of Lolium perenne L., Festuca rubra L., Festuca arundinacea Schreb., Poa pratensis L. and Poa annua L. aqueous extracts on germination rate and total germinability of Poa annua L. seeds and length of Poa annua L. leaves and roots was studied in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Cultivar studied and the donor -cultivar, even within one species. Differences in the strength of allelopathic interactions between different species and plant cultivars have also been demonstrated in other studies [24]. According to Kovar et al [24], these differences may be due to the diverse abilities of plants to synthesize allelopathic substances.…”
Section: Species (Donors)mentioning
confidence: 67%
See 1 more Smart Citation
“…Cultivar studied and the donor -cultivar, even within one species. Differences in the strength of allelopathic interactions between different species and plant cultivars have also been demonstrated in other studies [24]. According to Kovar et al [24], these differences may be due to the diverse abilities of plants to synthesize allelopathic substances.…”
Section: Species (Donors)mentioning
confidence: 67%
“…Differences in the strength of allelopathic interactions between different species and plant cultivars have also been demonstrated in other studies [24]. According to Kovar et al [24], these differences may be due to the diverse abilities of plants to synthesize allelopathic substances. The largest negative impact on the share of sown grass cultivars was recorded at the following sites (from greater to lesser negative impact): F. ovina 'Espro' , F. rubra ' Areta' , F. arundinacea ' Asterix' , and F. ovina 'Pintor' .…”
Section: Species (Donors)mentioning
confidence: 67%
“…annua. Kovár et al (2013) reported that certain turfgrass species affect germination, initial growth, and root development of P. annua. There is no information about the impact of bryophytes on this invasive species.…”
Section: Discussionmentioning
confidence: 99%